RENORMALIZATION FUNCTION FOR THE ELECTRON-FLEXURAL PHONON INTERACTION - GROSU, I. (Studia Universitatis Babeș-Bolyai Physica, 2018)
The renormalization function for the electron-phonon interaction is discussed. The system is considered as two-dimensional, and we consider the case of flexural phonons. The flexural phonons have a dispersion which is linear for wave-vectors less than a critical value q꜀ , and quadratic for q > q꜀. The renormalization function differs from the standard expression, and leads to modifications of the normal and superconducting properties of materials.